Cytotoxic Epstein–Barr virus‐positive large B cell lymphoma: a regulatory B cell‐derived neoplasia?. Issue 4 (20th December 2016) - Tabanelli, Valentina; Santiago‐Pacheco, Vanessa; Corbellino, Mario; Calleri, Angelica; Agostinelli, Claudio; Parravicini, Carlo; Pileri, Stefano A
Abstract : Aims: A new subtype of granzyme B (GrB)‐producing regulatory B cells (Bregs ) has been described recently; these peculiar cytotoxic B cells are increased significantly in interleukin (IL)‐21‐rich settings, and in particular during HIV and Epstein–Barr virus (EBV) infection. Our aim is to report a unique case of an EBV‐positive diffuse large B cell lymphoma (DLBCL) with cytotoxic features arisen in an HIV + patient, and to understand if this lesion may represent a proliferation of neoplastic cytotoxic Bregs . Methods and results: We describe a 66‐year‐old male patient who presented with cervical lymph node enlargement and B symptoms; subsequently, HIV infection was diagnosed. Histopathological, immunohistochemical and molecular studies were performed, and revealed an EBV‐positive DLBCL with cytotoxic features. Considering the immunological setting and unconventional phenotype observed, we tried to evaluate further the expression of GrB and IL‐21 in another 150 aggressive B cell lymphomas (17 of 150 EBV +, two of 150 EBV + /HIV + ). Minimal dot‐like expression of GrB was found in seven lymphomas (in fewer than 1% of tumour cells), three of which were EBV‐positive. Conclusions: Breg origin has never been reported in B cell lymphomas. We describe an exceptional case of EBV‐positive DLBCL with aberrant expression of cytotoxic markers in a patient with a previously unknown HIV infection. We propose cytotoxic Bregs as a possible normal counterpart for this unusual tumour.